Politically Connected Governments - CUNY, CHRISTINE; KIM, JUNGBAE; MEHTA, MIHIR N. (Journal of Accounting Research, 2020)
ABSTRACT This paper examines the consequences of powerful political connections for local governments. We find that governments located within the constituencies of, and thus connected to, powerful congressional members reduce their stewardship over public resources. Using plausibly exogenous declines in the power of congressional representation, we show that the effect is causal. To better understand why connected local governments can reduce stewardship, we study electoral characteristics. Our findings suggest that the increased resources that come with powerful congressional representation allow local‐government officials to reduce stewardship without material adverse effects on their reelection prospects. In sum, we provide evidence of a cost of political connections: they weaken local governments' incentives to act in a socially optimal manner.